Efficient incentives with social preferences - Thomas Daske; Christoph March (Bamberg University, Bamberg Economic Research Group (BERG), 2022)
This study explores mechanism design with allocation-based social preferences. Agents' social preferences and private payoffs are all subject to asymmetric information. We assume quasi-linear utility and independent types. We show how the asymmetry of information about agents' social preferences can be operationalized to satisfy agents' participation constraints. Our main result is a possibility result for groups of at least three agents: If endowments are sufficiently large, any such group can resolve any given allocation problem with an ex-post budget-balanced mechanism that is Bayesian incentive-compatible, interim individually rational, and ex-post Pareto-efficient.
Keywords: C72; C78; D62; D82; 330; mechanism design; social preferences; Bayesian implementation; participation constraints; participation stimulation